Rossiâ v 2012 skvozʹ prizmu konceptualʹnoj metafory - Balašova, Lûbovʹ V. (Stylistyka, 2019)
The author analyzes the regular types of conceptual metaphors used to characterize the results of social-economic and political development of Russia in 2012 at the pressconference by Vladimír Putin and by the representatives of the opposition in Internet publications.